Plateau Refractory Wounds Treated with Platelet Lysate Gel: A Case Report - ZHAO Qin; WANG Haiying; WANG Hui; ZHANG Jinjin; XING Yanchao (Xiehe Yixue Zazhi, 2024)
Plateau refractory wounds are affected by adverse conditions such as hypoxia, strong ultraviolet rays, and frigid, which can cause serious cell function damage, hinder re-epithelialization, and delay or even stop the healing of wounds. Conventional debridement and drainage, functional dressings and other traditional treatments have poor efficacy on this type of wound. Not only do patients have to endure long hospital stays, but they may also suffer from other complications due to long-term non-healing of wounds. In this paper, we report a patient with a plateau refractory wound that had not healed for 2 months. After two applications of platelet lysate gel treatment, the wound healed completely. This treatment method provides a new treatment approach for patients with plateau refractory wounds, which is worthy of clinical reference.